Transforming Educational Marketing in the Digital Era: Strategies for Utilizing Social Media to Increase the Competitiveness of Secondary Education Institutions - Masruroh, Emi; MF, Shafa; Hasanah, Uswatun (JUMPA : Jurnal Manajemen Pendidikan, 2023)
This research focuses on the implementation of educational marketing strategies through social media at SMP Fadhilatul Qur'an Ketapang, with the aim of analyzing the impact of these strategies on school visibility and competitiveness. This study uses a qualitative approach with phenomenological methods to understand the subjective experiences and perceptions of education actors related to the use of social media as a marketing tool. The data was collected through in-depth interviews, participatory observations, and analysis of social media content, involving various stakeholders at the school. The results show that the use of social media, particularly the Facebook and Instagram platforms, has significantly increased public engagement and strengthened the school's image in the community. The implications of this study show that marketing strategies through social media can be an effective tool to increase the competitiveness of educational institutions, as long as they are well managed and supported by adequate resources. This research contributes to the education management literature by offering a marketing model that is adaptive to the development of digital technology.